Thermal remanence of the ∼0.6 kya Rangitoto volcano eruption, Auckland volcanic field (New Zealand) inferred from self-potential and CO₂ flux measurements - Luthfian, Alutsyah; Finizola, Anthony; Mazot, Agnes; Adam, Ludmila; Gusset, Rachel; Eccles, Jennifer (Volcanica, 2025)
Rangitoto volcano is the most recent (⁓0.6 ka) and voluminous volcano in New Zealand’s Auckland Volcanic Field (AVF). In this study, we investigate the status of its hydrothermal system using a combination of self-potential (SP) and CO2 gas flux measurements along the west-east Rangitoto–Motutapu main road. SP data revealed a "W"-shaped signal near the main crater, indicating an active hydrothermal system. In contrast, the CO2 flux data showed diffuse emissions peaking ⁓620 m east of the SP anomaly peak, suggesting they originated from different sources. The SP anomaly is likely due to a hydrothermal system heated by a shallow, cooling basalt body, and CO2 emission is from deeper crustal or mantle sources. An SP electric potential offset was also detected at the Islington Bay Fault under the Rangitoto–Motutapu bridge without a corresponding CO2 flux anomaly. Résumé Le volcan Rangitoto est le plus récent (⁓0,6 ka) et le plus volumineux du champ volcanique d’Auckland (AVF)en Nouvelle-Zélande. Dans cette étude, nous avons évalué l’activité de son système hydrothermal en combinant mesures de polarisation spontanée (PS) et de flux de CO2 dans le sol le long de la route principale ouest-est Rangitoto–Motutapu. Les données PS ont révélé une forme en « W » à proximité du cratère principal, indiquant la présence d’un système hydrothermal actif. En revanche, les données de flux de CO2 ont montré des émissions diffuses dont l’intensité maximum se situe à environ 620 m à l’est du pic de l’anomalie SP, suggérant qu’elles proviendraient de sources différentes. L’anomalie PS est probablement liée à un système hydrothermal chauffé par un corps basaltique peu profond se refroidissant, et les émissions de CO2 proviendraient de sources crustales ou mantelliques plus profondes. Un décalage du potentiel électrique PS a également été observé au niveau de la faille d’Islington Bay sous le pont Rangitoto-Motutapu sans anomalie de flux de CO2 correspondante.